Integration of III-V lasers on Si for Si photonics. (August 2019) - Tang, Mingchu; Park, Jae-Seong; Wang, Zhechao; Chen, Siming; Jurczak, Pamela; Seeds, Alwyn; Liu, Huiyun
Abstract: Development of Si photonic integrated circuits (PICs) has been impeded due to lack of efficient Si-based light-emitting sources. Because of their indirect bandgap, bulk Ge and Si are very inefficient at emitting light. Therefore, direct-bandgap III-V semiconductors have been extensively exploited for the active region of the lasers for PICs. Heterogeneous and monolithic integration of III-V semiconductor components on Si platforms have been considered as promising solutions to achieve practical on-chip light-emitting sources for Si photonics. This paper reviews the latest developments on telecommunication wavelength III-V lasers integrated on Si substrates, in terms of integration methods and laser performance.